Evaluasi Kenyamanan Termal dan Rekomendasi Desain Arsitektur pada Kawasan Waterfront Kota Manado Berbasis Temperature Humidity Index - Jefri Muhaling; Defie R. Wawointana; Kivly E. Sarajar (Mandalika Journal of Business and Management Studies, 2026)
The waterfront area of Manado City is a strategic public space serving as a center of community activities; however, the area's architectural characteristics dominated by hard materials, minimal shade vegetation, and high-rise building configurations that block sea breezes have caused thermal discomfort for users. This study aims to evaluate the level of outdoor thermal comfort in the waterfront area of Manado City using the Temperature Humidity Index (THI) approach and formulate applicable climate-adaptive architectural design recommendations. The method employed combines a quantitative descriptive analysis with an architectural analysis of the area. Secondary climatological data were obtained from the BMKG Sam Ratulangi Meteorological Station, while the area's architectural characteristics were analyzed based on mass arrangement, building envelope materials, vegetation, and building orientation. Results show that the monthly THI values range from 25.62 to 26.45 with an annual average of 26.00; 50% of months fall within the "partially comfortable" category, and 50% are classified as "uncomfortable." Architectural factors causing discomfort include the dominance of high thermal-capacity materials, absence of shading elements, and building mass arrangements that obstruct sea breeze circulation. Based on these findings, this study proposes architectural design recommendations including: layered shade vegetation arrangement, application of pergolas and structural canopies, integration of water features in the landscape, use of porous high-albedo materials, and implementation of secondary skin and vertical gardens on building envelopes.